Recent progress in diatom genomics and epigenomics. (April 2017) - Tirichine, Leila; Rastogi, Achal; Bowler, Chris
Highlights: Diatom genomes are chimeric harboring genes derived from multiple origins. Diversity and abundance of diatoms in modern oceans. How molecular tools have boosted research in diatom genomics and epigenomics. Diatoms share features with plants and animals but also display specific ones. Abstract : Diatoms are one of the most diverse and successful groups of phytoplankton at the base of the food chain, sustaining life in the ocean and performing vital biogeochemical functions. The last fifteen years have witnessed the comprehensive analysis of several diatom genomes, revealing that they bear traces of their endosymbiotic origins from algal and heterotrophic ancestors, as well as significant gene transfer from bacteria. Their chimeric genomes are further regulated by a range of chromatin-based processes that are characteristic of both plant and animal genomes. We discuss the conservation of gene regulatory mechanisms in diatoms and propose that epigenetic processes may have a significant role in mediating responses to a highly dynamic and unpredictable environment in these organisms.